An approach to the study of the nutritive value of mulberry leaf and palm oil in growing pigs - González, Carlos; Tepper, Ricardo; Ly, Julio (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Forty eight crossbred castrated male pigs averaging 32 kg initial weight were employed according to a random block design arranged in a factorial 3 í—4 experiment to determine total tract digestibility coefficients of diets formulated to contain 0, 10 and 20% of mulberry (Morus alba) leaf meal and 0, 3, 6 and 9% of crude palm (Elaeis guineensis Jacq.) oil. Feed intake was fixed as 0.08 g DM/kg0.75 per day given in two daily equal rations. The mulberry leaf meal contained crude protein (N í—6.25) 14.50 and NDF 34.55% and 17.81 kjoule/g on dry matter basis respectively. There was no significant interaction (P > 0.05) between mulberry foliage meal and crude palm oil levels in any digestibility index. Overall, digestibility indices were high. Increasing levels of mulberry leaf meal in diet had a significant (PÂ < 0.01) negative influence on DM, organic matter, NDF, N and energy respectively, This same trend, although not significant (P > 0.05) was observed for increasing levels of crude palm oil in the diet on digestibility indices of pigs. N and organic matter digestibility of mulberry as determined by difference were 43.65 and 64.65 % respectively, whereas digestible energy accounted for 9.41 kjoule/g DM. Digestible energy estimated for the crude palm oil was rather low 16.12 kjoule/g DM). It is suggested that mulberry leaf meal could be introduced up to 20% in diets for growing pigs with no deleterious influence on total tract digestibility indices. The use of palm oil up to 9% can contribute to increase the energy density of the diet. Due to the relatively low digestibility of crude palm oil, methods should be investigated in order to improve its nutritive value.